Bilateral asymmetry in bullfrog testes and fat bodies: correlations with steroidogenic activity, mast cells number and structural proteins - Dias, Andressa Baggio [UNESP]; de Oliveira, Salmo Azambuja; Cerri, Paulo Sérgio [UNESP]; Sasso-Cerri, Estela [UNESP] (Elsevier, 2022)
In seasonal breeders, such as amphibians, testicular functions depend on complex processes that change according to seasonality, including Leydig cell (LC) differentiation and lipid-dependent steroidogenesis, extracellular proteins remodeling and actin-dependent cellular dynamics. Speculating that fat bodies (FB) could support some of these processes in L. catesbeianus, we evaluated bilaterally the FB weights, correlating them to testicular parameters such as weight, testosterone (T) immunoexpression, mast cells (MC) number, vascularization and structural proteins. In an attempt to better understand the testicular asymmetry in amphibians, correlations between these different testicular parameters were also established. Right testes (RT), left testes (LT) and associated FB of bullfrogs were weighed, and testes were processed for light and transmission electron microscopy. Collagen content (COL) and MC number were quantified. T and actin immunoexpressions and vascular areas were measured. Statistical analyses and Pearson's correlation were performed. The LT and its associated FB were heavier than the right ones, and showed intense T and actin immunoexpressions, numerous lipid-rich LC, and greater MC number, COL and vascularization than the RT. Positive correlations were detected between: a) FB and testis weights, b) T immunoexpression and testis and FB weights, c) T and actin immunoexpressions and COL. Otherwise, MC number was inversely correlated to T immunoexpression and COL. In right and left sides, the proportional correlation between T immunoexpression and FB weight suggests that FB-stored lipid amount depends on the steroidogenic demand of its associated testis. Thus, the asymmetry in the testes and FB may be associated, at least in part, to the LC steroidogenic activity, which tends to be more intense in LT than in RT. The results also point to a role of COL and mast cells in the LC differentiation and steroidogenesis. Actin was also greater in LT and correlated with T immunoexpression, indicating that the amount of this structural protein depends on androgenic control. Therefore, the testicular asymmetry in bullfrogs seems to be associated to different morphofunctional processes occurring, bilaterally, at different intensities. In this case, there is a tendency of LT, in association with its FB, to be more active than RT. The findings highlight the FB-testis interplay for the comprehension of reproduction in amphibians.
Keywords: Actin; Bioindicators; Collagen; Mast cells; Steroidogenesis; Testosterone